Calix(4)pyrrolato stannate(II): a tetraamido tin(II) dianion and strong metal-centered σ-donor - Ruppert, Heiko; Greb, Lutz (Angewandte Chemie. International edition, 2022)
Anionic, metal-centered nucleophiles are emerging compounds with unique reactivities. Here, we describe the isolation and full characterization of the first tetraamido tin(II) dianion, its behavior as ligand towards transition metals, and its reactivity as a tin-centered nucleophile. Experimental values such as the Tolman electronic parameter (TEP) and computations attest tin-located σ-donor ability exceeding that of carbenes or electron-rich phosphines. Against transition metals, the stannate(II) can act as η1- or η5-type ligand. With aldehydes, it reacts by hydride substitution to give valuable acyl stannates. The reductive dehalogenation of iodobenzene indicates facile redox pathways mediated by halogen bond interaction. Calix[4]pyrrolato stannate(II) represents the first example of this macrocyclic ligand in low-valent p-block element chemistry.
First published: 12 January 2022
Gesehen am 04.10.2022